1990
DOI: 10.1159/000117334
|View full text |Cite
|
Sign up to set email alerts
|

Single Photon Emission Computed Tomography with Technetium-99m Hexamethyl Propylenamino Oxime in the Pain-Free Interval of Migraine and Cluster Headache

Abstract: Thirty-three headache-free patients (19 F/14 M) suffering from common (n = 9) and classic migraine (n = 19) as well as cluster headache (n = 5) were investigated using the flow tracer 99mTc-hexamethyl propylenamino oxime and single photon emmission computed tomography. A regional decrease of cerebral tracer uptake was observed in 16 patients with common migraine, but only in 3 patients with classic migraine and in no patient with cluster headache. In 10 of 15 cases with hemiplegic symptoms during mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Such findings, which may reflect diffuse axonal injury and inflammation, are also consistent with several other studies of headache and pain syndromes [47], [48], [49]. An early study reported decreased cerebral blood flow is associated with common migraines suggesting that migraine attacks occur in connection with exacerbations of preexisting changes of neuronal activities, cerebral perfusion and metabolism [50]. In addition, in our study, low CBF in the left frontal lobe and right temporal lobe correlated with poorer reported physical health.…”
Section: Discussionsupporting
confidence: 89%
“…Such findings, which may reflect diffuse axonal injury and inflammation, are also consistent with several other studies of headache and pain syndromes [47], [48], [49]. An early study reported decreased cerebral blood flow is associated with common migraines suggesting that migraine attacks occur in connection with exacerbations of preexisting changes of neuronal activities, cerebral perfusion and metabolism [50]. In addition, in our study, low CBF in the left frontal lobe and right temporal lobe correlated with poorer reported physical health.…”
Section: Discussionsupporting
confidence: 89%
“…It was suggested that this may be because an equivalent regional analysis was not performed in this study. A number of other studies also have reported interictal abnormalities [32][33][34].…”
Section: Interictal Changesmentioning
confidence: 85%
“…Fundamental to the concept of idiopathic or primary headache, including migraine, tension-type headache, and [46] 1978 CH Xenon 133 9 ↑ Schlake et al [47] 1990 CH Tc 99m HM-PAO 5…”
Section: Morphometric Studies: Pointing Toward a Lesionmentioning
confidence: 99%